Pemanfaatan dan Permasalahan Artificial Intelligence Dalam Kehidupan Manusia Serta Pengaturannya Secara Hukum - Akbar, Muhammad Dafi; Sihotang, Josua Ferdinand; Purnama, Rendika; Hasna, Taria (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was conducted to obtain information, including theories, concepts, legal principles and legal regulations. In using primary legal materials, this article uses materials, namely the ITE Law of 2008 Jo. 2023 as well as secondary legal materials, namely books, articles and legal journals providing further explanation of primary legal materials. This includes draft laws, research results, and opinions of legal experts. This research was conducted using normative juridical research (normative legal research method). The normative juridical research method is library legal research which is carried out by examining library materials or mere secondary data. The era of the Fourth Industrial Revolution has entered the digital era where Artificial Intelligence (AI) plays an important role in transforming various aspects of human life, including the legal realm. While AI offers many benefits, its utilization also raises significant concerns and challenges, particularly in the context of legal regulations and ethical considerations. In Indonesia, even though AI technology is experiencing rapid progress, there is still no specific legal framework that addresses its existence and implications. The Information and Electronic Transactions Law (UU ITE) provides the basis for regulating electronic systems, including AI, although indirectly. AI is categorized under electronic systems and electronic agents according to Indonesian law. This classification implies that AI operates under the control and responsibility of a human operator or system provider.